The objective evaluation of triamcinolone acetonide efficacy in keloids management using Antera3D® imaging system - Fedele Lembo; Liberato Roberto Cecchino; Domenico Parisi; Aurelio Portincasa (SAGE Publishing, 2022)
Background Keloids are pathological scars characterized by nodular fibrous tissue that extends beyond the border of initial damage. These lesions do not spontaneously regress and can cause cosmetic disfigurements and functional disabilities. IntraLesional Injection of Triamcinolone Acetonide (ILITA), alone or in combination with other therapy, is one of the first-line treatment modalities. In this study the authors evaluated the objective efficacy of ILITA treatment in keloids management using this new imaging system. Materials and Methods 37 patients with 45 keloid scars were treated with intralesional injection of triamcinolone acetonide (TAC) 20 mg/ml at an interval of three weeks. Antera3D® camera took the images and dates of the treated area in each patient, before the treatment (T0) and at three weeks after the last injection (T1). The system processed the levels of color, elevations, melanin and hemoglobin expression. All the scars were also evaluated, at the same times, by validated Vancouver Scar Scale (VSS). Comparison of the variables was performed using a Wilcoxon signed-rank test with a p < 0.05. Results At T0, mean VSS score was 8.67 ± 1.35 which reduced to 3.62 ± 1.72 at final follow up. Antera3D® scores were statistically significant differences in color (8.14 ± 2.41 vs 9.54 ± 1.81), protrusion (381.3 ± 15.6 vs 198.6 ± 21.3), melanin (0.53 ± 0.02 vs 0.62 ± 0.2) and hemoglobin (1.26 ± 0.41 vs 2.21 ± 0.41) expression levels after the treatment. Conclusions In our clinical trial, the data results demonstrated that ILITA seems to be effective in reducing keloid dimensions and symptoms such as itching and pain, even if the treatment has local minimal adverse effects such as pain, telangiectasias and atrophy. Lay Summary Keloids are pathological scars characterized by nodular fibrous tissue that extends beyond the border of initial damage. Large keloids can cause cosmetic disfigurements and functional disabilities that affect quality of life. In literature, several treatment approaches have been described but, to date, no single method is considered superior. The International Advisory Panel on Scar Management recommended the use of intralesional steroid injections for keloids treatment. The efficacy of treatment may be evaluated with subjective scale; as no one can guarantee an objective evaluation. To eliminate the observer and/or patient factors, and to obtain a reliable, consistent, feasible, valid and objective evaluation a skin analysis camera system called Antera3D® (Miravex, Dublin, Ireland) can be used. In this study the authors evaluated the objective efficacy of triamcinolone acetonide treatment in keloids management using this imaging system. In this series, for Antera3D® scores there were statistically significant differences in color, protrusion, melanin and hemoglobin expression levels before and after treatment. The device directly shows the treatment changes, measured objectively and accurately, without bias of traditional evaluation scoring scale. Antera3D® system guarantees an objective evaluation of effectiveness of scar treatment enabling clinicians to modulate the therapy according to the scores registered.